Relationship between Test Anxiety and Academic Achievement of Students in Science at Secondary Level, in Islamabad - Shahzad Ahmad; Sadia Jamil; Saba Fatima (JCTE, 2025)
Understanding students’ test anxiety is very important for teaching and learning activities. The present study was intended to determine secondary school students’ test-related anxiety and its relationship with their academic achievement both in terms of gender and locality. A descriptive and correlational research design was used to collect the data. The sample of the study consisted of 440 students out of which 215 were male students and 225 were female students from 6 urban and 7 rural secondary schools in Islamabad, Pakistan. Students’ academic achievement was measured through the marks obtained by them in the recently held board examination. Initially, the research instrument to measure students’ test anxiety in science which was developed by Spielberger in 1980 and then used by Stefan Peter and Philip Zabek, consisted of 40 items. After slight modification and cultural adaptation, a 29-item Likert-type scale was developed and validated by the author. The obtained data were analyzed and interpreted using various statistical techniques like mean, standard deviation, Pearson product-moment correlation, independent sample t-test, and two-way ANOVA. The findings revealed that overall, a majority of students showed a neutral attitude towards test anxiety, very few numbers of students have a negative response, and hardly anyone exhibited a positive response towards test anxiety in science. The present study showed a negative relationship between test anxiety and the academic achievement of students in science. These findings imply that increased test anxiety reduces student academic achievement. Further, it was concluded that there exists a gender and locale effect on students’ test anxiety and their academic achievement in science.